Disclosure and the cost of capital - Koopman, Anthony C (Department of Finance and Tax, 2024)
[pg 11 is missing] In both academic literature and business practice there appears to be contradictory views concerning the existence, and nature, of the relationship between the quality of corporate disclosure and associated company cost of equity capital. Theory suggests that an informed investor would scale down the required rate of return as the level of uncertainty and risks associated with the firm's present and future performance is reduced. This study has attempted to empirically determine whether or not South African companies manage the level of information disparity between investors and themselves so as to influence the company's cost of capital. A literature study was undertaken to ascertain what data and empirical findings have been produced by previous studies on disclosure and the cost of capital. The literature review also highlighted the impact that information asymmetry, intra-industry information transfers, estimation risk and information filtering by management has on disclosure and the effect that this has on cost of capital. The firms beta coefficient, based on the last quarter of 1997, were used as a measurement of risk and as a surrogate for the cost of capital. The disclosure metric was based on the financial and non-financial information contained in the 1997 annual financial reports of the sample companies. The research method that was adopted builds on both local and international empirical research in this field, using a statistical correlation analysis to test the null hypothesis of no relationship between disclosure and beta for companies listed on the Johannesburg Stock exchange. The research results provided evidence of a positive, yet very weak correlation between disclosure and the cost of capital. As the variation in the sample data improved, a slightly stronger positive correlation between the research variables was observed.